Discussion of the state of the art of the cane’s market - Pereira, Tiago (2016)
This paper approaches the cane's market and identifies some of its flaws. Walking sticks are a very common asset due its simplicity and ease of use, however at times it can be a dangerous, unreliable object and cause serious injuries. Due to canes' popularity between mobility aids there is a need of improvement in security and stability. This work reviews the cane's state-of-the-art considering the relevant features. Both commercial solutions as well as academic research have been considered. Search included patents related with walking stick. There is also an observation about health issues that come from canes daily use. The article summarizes these features and proposes a new cane, with proposed improvements to the common cane, in order to obtain a better use of the cane, avoiding risks and flaws from the use of the cane that are harmful to the health. This model is largely biomechanical inspired in the human gait.